On the relationship between firm size, resources, age at entry and internationalization: the case of Slovenian SMEs - Ruzzier, Mitja; Konecnik Ruzzier, Maja (Journal of Business Economics and Management, 2014)
Export marketing and international business literature support the view that firm size–a reflection of number of employees, and sales–is positively related to export intensity and is a distinguishing factor between internationalized and non-internationalized firms. According to the resource-based view heterogeneous resource profiles that enable firms to achieve competitive advantage in international markets may be also such differentiating factors. On the other hand, as a result of the process of globalization and the increasing number of born global firms, firm age at entry into foreign markets is becoming negatively related to internationalization. Our findings just partly confirm the trends above. Using a regression model on the selected sample of 247 Slovenian small and medium enterprises, we have confirmed the hypotheses that internationalized companies are significantly larger (in terms of sales) and have more specialized resources (human, organizational, and financial resources) than non-internationalized companies. Organizational and human resources and the number of employees were positively and significantly related, while the age of companies at the start of their international activities was negatively related, to the extent of companies’ internationalization. Different implications and conclusions for researchers and entrepreneurs are derived.